2006
DOI: 10.1159/000091783
|View full text |Cite
|
Sign up to set email alerts
|

Acute-on-Chronic Renal Failure in the Rat: Functional Compensation and Hypoxia Tolerance

Abstract: Background: We hypothesized that chronic renal parenchymal disease may predispose to acute renal failure (ARF), facilitating the induction of hypoxic medullary tubular injury. Methods: To induce chronic renal parenchymal injury, rats underwent sham operation (control) or bilateral 50-min clamping of the renal artery [ischemia-reperfusion (IR)]. One or 3 months later, both groups were subjected to an ARF protocol, consisting of radiocontrast and the inhibition of prostaglandin and nitric oxide synthesis. Renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
64
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 50 publications
9
64
0
Order By: Relevance
“…We also found that HIF-α isoforms are stabilized in acute hypoxic stress, predominantly in the cortex in rhabdomyolysis-induced kidney injury [26], in the outer stripe of the outer medulla following ischemia and reperfusion [27,28], or in the inner stripe and inner medulla following the induction of distal tubular hypoxic injury by radiocontrast agent, or after the inhibition of prostaglandin or NO synthesis or with their combinations [23]. Outer medullary HIF stabilization is also noted in chronic tubulointerstitial disease [29] and in experi mental diabetes [30], again spatially distributed in areas with proven hypoxia. HIF was also detected in biopsies from transplanted kidneys [31].…”
Section: Hif Expression Under Hypoxic Stress and Tissue Injurymentioning
confidence: 60%
“…We also found that HIF-α isoforms are stabilized in acute hypoxic stress, predominantly in the cortex in rhabdomyolysis-induced kidney injury [26], in the outer stripe of the outer medulla following ischemia and reperfusion [27,28], or in the inner stripe and inner medulla following the induction of distal tubular hypoxic injury by radiocontrast agent, or after the inhibition of prostaglandin or NO synthesis or with their combinations [23]. Outer medullary HIF stabilization is also noted in chronic tubulointerstitial disease [29] and in experi mental diabetes [30], again spatially distributed in areas with proven hypoxia. HIF was also detected in biopsies from transplanted kidneys [31].…”
Section: Hif Expression Under Hypoxic Stress and Tissue Injurymentioning
confidence: 60%
“…In such models, despite a more prominent reduction of GFR after the injection of the radiocontrast, the extent of ATN was not intensified as compared with control animals that were subjected to similar radiocontrastmediated hypoxic insults (43,54). Conceivably, chronic HIFmediated hypoxia adaptation provides acute hypoxia tolerance.…”
Section: Hypoxia Stress Response and Hypoxia Adaptationmentioning
confidence: 98%
“…Conceivably, chronic HIFmediated hypoxia adaptation provides acute hypoxia tolerance. Importantly, in an acute-on-chronic renal failure model of CIN, declining GFR was mostly predicted by the extent of chronic tubulointerstitial disease, whereas medullary hypoxic tubular injury could be correlated with evolving tubular dysfunction, such as defects in urine concentrating capacity and sodium transport, assays not routinely used in clinical practice (54).…”
Section: Hypoxia Stress Response and Hypoxia Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many hypoxiatriggered HIF-dependent protective effectors such as EPO and VEGF rise, which counteracts the effect of the harmful pathways, promoting angiogenesis, improving tissue oxygenation and cell survival, and facilitating homing of progenitor cells. 121 In fact, rats with chronic tubulointerstitial disease 122 or diabetes 123 have shown unpredicted resistance to acute hypoxic insults, possibly through hypoxia tolerance, induced by HIFmediated pathways. However, diabetic kidneys subjected to extreme hypoxic conditions, such as warm ischemia reflow 124 or ex vivo perfusion with red cellfree perfusate, 123 are highly exposed to hypoxic damage, which suggests that HIF-mediated renoprotection is ineffective beyond a "window of opportunity" of moderate acute hypoxic stress.…”
Section: Renal Hypoxia Response: Bad and Good Componentsmentioning
confidence: 99%